2021
DOI: 10.1016/j.copsyc.2020.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Are we any closer to identifying a causal relationship between cannabis and psychosis?

Abstract: The increasing availability of high potency cannabis increases the risk of developing cannabis psychosis, as a dose response relationship has been established as a risk factor. • Defining and standardizing terms and measurement of cannabis products and use could usefully transform research and practice for cannabis psychosis.• Evidence based interventions for patients with cannabis psychosis are limited and those that show promise are symptom-specific rather than treating all symptoms.• Liberalisation of canna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…rare) negative responses to psychedelics, and acute psychotic or psychosis-like symptoms might be regarded in this way, i.e., one of the more severe possible responses to psychedelics or cannabis. This matter seems especially relevant given literature on the psychotomimetic effects of both cannabis and psychedelics (Carhart-Harris et al 2013 ), as well as complex questions over the psychotogenic potential of cannabis use (Hamilton and Sumnall 2021 ). We hope that through reporting on the subjective effects of psychedelics use in combination with cannabis, we can contribute to raising awareness among recreational users, allowing them for better informed decision making; an especially important feature of harm reduction strategies in adolescents (Baltzer et al 2008 ), who are the most susceptible group to experience negative effects of cannabis on their mental wellbeing (Gobbi et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…rare) negative responses to psychedelics, and acute psychotic or psychosis-like symptoms might be regarded in this way, i.e., one of the more severe possible responses to psychedelics or cannabis. This matter seems especially relevant given literature on the psychotomimetic effects of both cannabis and psychedelics (Carhart-Harris et al 2013 ), as well as complex questions over the psychotogenic potential of cannabis use (Hamilton and Sumnall 2021 ). We hope that through reporting on the subjective effects of psychedelics use in combination with cannabis, we can contribute to raising awareness among recreational users, allowing them for better informed decision making; an especially important feature of harm reduction strategies in adolescents (Baltzer et al 2008 ), who are the most susceptible group to experience negative effects of cannabis on their mental wellbeing (Gobbi et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In addition, a large body of epidemiological evidence (utilizing a range of research designs) has demonstrated a directional dose-response association between cannabis use and incidence of schizophrenia, with the association being more pronounced among individuals reporting early adolescent initiation, those with a high genetic loading for psychotic illnesses, and persons reporting prior psychotic symptoms. [6][7][8][9] Experimental pharmacological challenge involving patients with schizophrenia has shown that administration of THC worsens psychotic symptoms (e.g., D'Souza et al 2005), 10 while clinical studies (for a systematic review, see, Schoeler et al 2016) 11 have found that the continuation of cannabis use after the onset of psychotic illness is associated with worse outcomes-including higher relapse rates, longer hospital stays, and more pronounced positive psychotic symptomology, in comparison to those patterns observed among people with psychosis who discontinue or abstain from cannabis use. It is important to acknowledge, however, that only a small proportion of cannabis users identified in populationbased surveys report any past-year problems related to their cannabis use.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effectiveness of education and information strategies in reducing cannabis-related harm such as psychosis may be limited. Providing products with a balanced THC:CBD ratio that is still attractive to consumers may be a more effective way of minimising harm (Hamilton & Sumnall, 2021).…”
Section: Education and Informationmentioning
confidence: 99%
“…Factors that increase the risk of psychosis also include the consumption of cannabis strains high in THC and low in cannabidiol (CBD; Hamilton & Sumnall, 2021). THC is the main psychoactive constituent that acts on the CB1 receptor to produce relaxation and euphoria (Green et al, 2003).…”
Section: The Mental Health‐related Impacts Of Cannabis Usementioning
confidence: 99%
See 1 more Smart Citation